Performance Evaluation and Operational Optimization of a Fine-Bubble Porous–Venturi Aeration System - Niesa Hanum Mistoro; Sri Puji Saraswati; Johan Syafri Mahathir Ahmad; Henny Sudibyo; Dahlia Anggita Zahra (Universitas Diponegoro, 2026)
Aeration is the most energy-intensive unit in wastewater treatment systems, particularly in shallow decentralized reactors with limited hydrostatic pressure, which, which reduces oxygen transfer efficiency. However, systematic evaluations of integrated porous–Venturi microbubble systems under shallow-water conditions are limited. This study aims to address this gap by investigating and optimizing a fine-bubble porous–Venturi microbubble generator (MBG) using laboratory-scale experiments. Clean water experiments were conducted in a 200 L batch reactor with two liquid flow rates (71.6 and 103.8 L/min) and four gas flow rates (0.15–0.60 L/min). Aeration performance was assessed using the volumetric oxygen mass transfer coefficient (KLa(20)), standard oxygen transfer rate (SOTR), and specific aeration efficiency (SAE), supported by one-way ANOVA. The results showed that the gas flow rate influenced KLa(20) and SOT,R whereas the liquid flow rate had a dominant effect on SAE. The optimal operating conditions were identified as QL = 71.6 L/min and QG = 0.45 L/min, achieving KLa(20) of 2.23 h⁻¹ and SAE exceeding 40 kg O₂/kWh. The findings showed that optimum gas–liquid interaction leads to energy-efficient aeration performance rather than maximum flow rate supply. It also provides practical design insights for optimizing aeration systems in shallow and decentralized wastewater treatment applications